(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Sugar-sweetened beverage (SSB) consumption has been estimated to be the highest in sub-Saharan Africa, with a significant impact on the increasing burden of diet-related non-communicable diseases among adolescents. This manuscript highlights the research plan and procedures for SSB consumption among adolescents in Nigeria (SURRENDER), a survey designed to assess the magnitude and patterns of sweetened beverages (SSB) consumption with its associated factors and the potential association with cardiometabolic risk factors, including obesity, high blood pressure and elevated blood sugar, among in-school adolescents in Nigeria. The SURRENDER study surveyed in-school adolescents (males and females, aged 10–19 years) from secondary schools across three main cities: Abuja, Ikeja, and Ibadan, Nigeria. Participant enrollment, including questionnaire administration, physical examination and blood specimen collection, started in 2023, using the World Health Organization’s STEPS Instrument for Chronic Disease Risk Factor Surveillance for data collection. Data were collected on sociodemographics, parent and family characteristics, lifestyle factors, food access and dietary diversity, SSB consumption, physical and sedentary activity, school environment, anthropometric measurements (including weight in kilograms, height and mid-upper arm circumference in centimetres) and blood pressure assessment (including systolic and diastolic blood pressure and pulse rate) and blood glucose measurements by trained personnel in keeping with standing protocol, procedures and tools. A total of 1,699 (females – 58.6%) were recruited (29.4% - Abuja, 29.4% - Ikeja and 41.1% - Ibadan) with a 74.9% response rate and focused group discussions are underway to understand the etiological basis for perceptions, attitudes, and environmental drivers of dietary SSB consumption among adolescents. The SURRENDER would be promising, as it would provide evidence-based and innovative data that would ultimately inform the design of public health guidelines, advisories, and policy initiatives to support strong adolescent health in Nigeria and can be extrapolated for guidance in other African countries